1984
DOI: 10.1086/131310
|View full text |Cite
|
Sign up to set email alerts
|

The barium stars

Abstract: The barium stars are Population I G-K giants that have enhanced abundances of carbon and s-process elements, and are probably related in their peculiarities to several other carbon enhanced red-giant types such as CH, R, N, and S stars. Since the abundance anomalies in the barium stars are likely the result of mixing of processed material from deep within a stellar interior, and since they are numerous with many bright examples suitable for detailed observations, these stars provide very valuable information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 17 publications
2
54
0
Order By: Relevance
“…This has been confirmed by McClure (1983McClure ( , 1984 and Udry et al (1998a,b). Böhm-Vitense (1980) and Böhm-Vitense & Johnson (1985) observed an ultraviolet excess in the barium stars ζ CAP and ξ Ceti, which could be explained by white dwarf companions.…”
Section: Introductionsupporting
confidence: 61%
“…This has been confirmed by McClure (1983McClure ( , 1984 and Udry et al (1998a,b). Böhm-Vitense (1980) and Böhm-Vitense & Johnson (1985) observed an ultraviolet excess in the barium stars ζ CAP and ξ Ceti, which could be explained by white dwarf companions.…”
Section: Introductionsupporting
confidence: 61%
“…This is the explanation for blue stragglers in clusters (McCrea 1964), Ba-stars, and extrinsic C-stars (McClure et al 1980;McClure 1984;McClure & Woodsworth 1990). Different signatures can be observed, depending on when and how much mass was transferred from the donor (in our case the WD).…”
Section: Abundance Analysismentioning
confidence: 74%
“…Bidelman (1985) obtained a frequency between 0.5 and 1%. Most Ba-stars are in binary systems with orbital periods typically longer than 100 days but shorter than 10 years (McClure et al 1980;McClure 1984;McClure & Woodsworth 1990), though Jorissen et al (1998) reported a few cases with periods outside this range. Orbits typically have low but nonzero eccentricity, because they are most likely not produced by Roche-lobe overflow; the origin is probably due to stellar wind.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the stars for which no radial velocity variability was found belonged to the mild barium class. A firm conclusion was not possible although they mostly seemed to be members of a binary system (McClure 1984).…”
Section: The Mild Barium Starsmentioning
confidence: 96%